The remarried empress. 6 - Alphatart (Novelist) (Ize Press, 2024)
"I HAVE NO INTENTION OF GRANTING MY EX-WIFE THE RIGHT TO REMARRY." Navier and Heinrey have agreed to marry! Heinrey is over the moon, despite the political nature of their initial arrangement, but Navier is still reeling from Sovieshu's decision to separate. She must scramble to recover, though, knowing full well that the emperor will do everything in his power to prevent their union. And so, when the day of the formal trial arrives, Navier brandishes her and Heinrey's trump card-"I accept this divorce... and request an approval for my remarriage!"